Estimation of Postmortem Interval by Measuring Potassium Level in Vitreous Humour - Bohra, Bhavesh; Verma, Ramakant; Mathur, Indu Bala; Sharma, Yogesh; Khangwal, Vijay Pal; Joshi , Manoj (Journal of Indian Academy of Forensic Medicine, 2015)
Establishing the postmortem interval is one of the difficult challenges faced by forensic experts, particularly when limited information about deceased is available. Various methods have been tried to find out the time of death. These include study of physical, chemical, biochemical, histological and enzymatic changes which occur progressively in dead body. The chemical changes to determine the postmortem interval have been increased largely in the last few decades, which are based on changes occurring in the body immediately or shortly after death. These changes occur in various body fluids such as whole blood, serum, CSF, aqueous and vitreous humour. In this study vitreous humour potassium concentration were investigated to predict postmortem interval. In this study we have observed linear rise of vitreous potassium (K+) ion concentration with increasing post-mortem interval that was both arithmatic as well as logarithmatic (statistically) significant. No significant differences existed for vitreous potassium concentration in the same pair of eyes at identical post-mortem interval. Factors like age, sex, cause of death and environmental temperature did not influence the vitreous humour potassium values.